2015
DOI: 10.11113/jt.v72.3908
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Mathematical Model of Entrepreneurship Based on Transformational Leadership Behavior

Abstract: This study aimed to reduce the university-industry gap from the perspective of leadership and entrepreneurship. The focus of this research is to assess the influence of transformational leadership of manager on academic staff’s entrepreneurial orientation and to pave the way for identifying potential opportunities, generating new ideas in industrial relation, and to subsequently narrow the university-industry problem. In order to understand the contribution of leadership within the university–industry context,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A structure model was constructed to indicate the path among the factors in accordance with the hypothesis, H2, for factors estimated by the measurement model [57]. The initial structure model was tested by rearranging the pathways, as presented in Figure 4.…”
Section: Structural Modelmentioning
confidence: 99%
“…A structure model was constructed to indicate the path among the factors in accordance with the hypothesis, H2, for factors estimated by the measurement model [57]. The initial structure model was tested by rearranging the pathways, as presented in Figure 4.…”
Section: Structural Modelmentioning
confidence: 99%
“…The authors concluded that while the academic entrepreneurial ecosystem is flourishing in Iran, some improvements must be made to further nurture the academic entrepreneurship environment. In other work, Rashed et al (2015) applied the structural equation model (SEM) in two steps to develop a mathematical model of entrepreneurship. This study, which had as a focal point the impact of transformational leadership behavior, revealed transformational leadership quality as having enormous influence over entrepreneurial practice.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…However, little attention has been paid to researching the key attributes of EC and of the start-up dimension (Hallam et al , 2017). Recently, many governments across the world, and in particular ASEAN-05 Governments, have emphasized the EC environment in their economic development missions (Rashed et al , 2015). Currently, a vast majority of entrepreneurship researchers assert that theoretical and empirical research on EC is needed to improve the consistency and relevance of future studies on this topic (Bergmann et al , 2014).…”
Section: Introductionmentioning
confidence: 99%